Evaluating the protective potency of Acacia hydaspica R. Parker on histological and biochemical changes induced by Cisplatin in the cardiac tissue of rats - Tayyaba Afsar; Suhail Razak; Ali Almajwal; Maria Shabbir; Muhammad Rashid Khan (BMC, 2019)
Abstract Background Increase oxidative trauma is the main cause behind Cisplatin (CP) induced cardiotoxicity which restricts its clinical application as anti-neoplastic prescription. Acacia hydaspica is a natural shrub with diverse bioactivities. Acacia hydaspica ethyl acetate extract (AHE) ameliorated drug-induced cardiotoxicity in animals with anti-oxidative mechanisms. Current study aimed to evaluate the protective potential of A. hydaspica against cisplatin-induced myocardial injury. Methods Rats were indiscriminately distributed into six groups (n = 6). Group 1: control; Groups 2: Injected with CP (7.5 mg/kg bw, i.p, single dose) on day 16; Group 3: Treated for 21 days with AHE (400 mg/kg b.w, oral); Group 4: Received CP injection on day 16 and treated with AHE for 5 days post injection; Group 5: Received AHE (400 mg/kg b.w/day, p.o.) for 21 days and CP (7.5 mg/kg b.w., i.p.) on day 16; Group 6: Treated with silymarin (100 mg/kg b.w., p.o.) after 1 day interval for 21 days and CP injection (7.5 mg/kg b.w., i.p.) on day 16. On 22nd day, the animals were sacrificed and their heart tissues were removed. Cisplatin induced cardiac toxicity and the influence of AHE were evaluated by examination of serum cardiac function markers, cardiac tissue antioxidant enzymes, oxidative stress markers and histology. Results CP inoculation considerably altered cardiac function biomarkers in serum and diminished the antioxidant enzymes levels, while increased oxidative stress biomarkers in cardiac tissues AHE treatment attenuated CP-induced deteriorations in creatine kinase (CK), Creatine kinase isoenzymes MB (CK-MB), cardiac Troponin I (cTNI) and lactate dehydrogenase (LDH) levels and ameliorated cardiac oxidative stress markers as evidenced by decreasing lipid peroxidation, H2O2 and NO content along with augmentation in phase I and phase II antioxidant enzymes. Additionally, CP inoculation also induced morphological alterations which were ameliorated by AHE. In pretreatment group more significant protection was observed compared to post-treatment group indicating preventive potential of AHE. The protective potency of AHE was comparable to silymarin. Conclusion Results demonstrate that AHE attenuated CP induce cardiotoxicity. The polyphenolic metabolites and antioxidant properties of AHE might be responsible for its protective influence.